Implementation of Child-Friendly Madrasah Program - Sohani, Sohani; Umami, Mashlihatul (Jurnal Penelitian Pendidikan, 2025)
This study aims to describe the implementation of the Child-Friendly Madrasah Program at MIN 1 Semarang including the implementation, obstacles found, and solutions applied in implementing this program. This study uses a qualitative approach, a descriptive research type. The subjects of this study were the Head of Madrasah, Deputy Curriculum, teachers of MIN 1 Semarang, Students and Parents of MIN 1 Semarang. Data collection techniques were obtained from interviews, observations, and documentation. Data analysis techniques are: data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of the Child-Friendly Madrasah Program at MIN 1 Semarang has been carried out well, starting from preparation, planning, implementation, and evaluation. Furthermore, the obstacles found in implementing the Child-Friendly Madrasah at MIN 1 Semarang include internal and external obstacles. Internal obstacles include policies that are still not fully understood, the implementation of changing curricula, lack of trained educators and education personnel, facilities and infrastructure that do not meet needs, lack of children's participation space, and participation of parents and other parties that is not yet optimal. While external obstacles include limited support from the government and the community, limited access to technology and information, limited human resources, and lack of cooperation with other institutions. Related to the internal obstacles encountered, the solutions implemented by the madrasah are to collaborate with related parties and create clear policies, revise the curriculum every year according to needs, conduct dissemination and training, complete facilities and infrastructure gradually, provide wider opportunities for children to participate more, and embrace and maximize the role space that exists in the parent-teacher association. Meanwhile, solutions to external obstacles include strengthening communication more intensively, educating and socializing the use of gadgets wisely and correctly, holding training and workshops or the like, and improving communication and collaboration with related parties.